A Role for NF-κB in Organ Specific Cancer and Cancer Stem Cells - Kaltschmidt, Christian (Cancers (Basel), 2019)
Cancer stem cells (CSCs) account for tumor initiation, invasiveness, metastasis, and recurrence in a broad range of human cancers. Although being a key player in cancer development and progression by stimulating proliferation and metastasis and preventing apoptosis, the role of the transcription factor NF-κB in cancer stem cells is still underestimated. In the present review, we will evaluate the role of NF-κB in CSCs of glioblastoma multiforme, ovarian cancer, multiple myeloma, lung cancer, colon cancer, prostate cancer, as well as cancer of the bone. Next to summarizing current knowledge regarding the presence and contribution of CSCs to the respective types of cancer, we will emphasize NF-κB-mediated signaling pathways directly involved in maintaining characteristics of cancer stem cells associated to tumor progression. Here, we will also focus on the status of NF-κB-activity predominantly in CSC populations and the tumor mass. Genetic alterations leading to NF-κB activity in glioblastoma, ependymoma, and multiple myeloma will be discussed.